GAMBARAN STRES AKADEMIK PADA MAHASISWA TEKNIK - Marselina Saputri; Kiky D. H. Saraswati (Fakultas Psikologi Universitas Tarumanagara, 2026)
Academic stress is a common psychological condition experienced by university students when academic demands are perceived as exceeding their personal capabilities. Engineering students are particularly vulnerable to academic stress due to intensive coursework, project-based assignments, laboratory activities, and high academic performance expectations. This study aimed to describe academic stress among engineering students based on demographic characteristics, including gender, age, semester level, and organizational involvement. This research employed a quantitative descriptive approach using a convenience sampling technique. The participants consisted of 150 engineering students from various universities in Indonesia. Data were collected using the Perceived Academic Stress Scale (PASS) developed by Bedewy and Gabriel, which demonstrated good reliability with a Cronbach’s Alpha coefficient of 0.834. Data analysis was conducted using descriptive statistics, the Kolmogorov–Smirnov normality test, and non-parametric difference tests, namely Mann–Whitney U and Kruskal–Wallis. The results indicated that the overall level of academic stress among engineering students ranged from moderate to high, as shown by an empirical mean score higher than the hypothetical mean. The findings revealed no significant differences in academic stress based on gender and age. However, significant differences were found based on semester level in certain dimensions of academic stress, particularly workload and examinations, as well as academic self-perception. These results suggest that increasing academic demands across semesters contribute to higher academic stress among engineering students. Therefore, universities are encouraged to provide adequate academic and psychological support to help engineering students manage academic stress more effectively.